2015
DOI: 10.1016/j.engfracmech.2015.03.045
|View full text |Cite
|
Sign up to set email alerts
|

A phase field method to simulate crack nucleation and propagation in strongly heterogeneous materials from direct imaging of their microstructure

Abstract: International audienceIn this work, crack initiation and propagation in 2D and 3D highly heterogeneous materials models, such as those obtained by micro-CT imagery of cementitious materials, is investigated for the first time by means of the phase field method. A shifted strain split operator algorithm is proposed to handle unilateral contact within cracks in a very efficient manner. The various advantages of the phase field method for voxel-based models are discussed. More specifically, we show that the resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 58 publications
0
138
0
Order By: Relevance
“…In (6) , γ(d, ∇d) is the crack density function per unit volume (see e.g. Miehe et al (2010);Nguyen et al (2015)), defined by:…”
Section: Phase Field Modeling Of Stress Corrosion Crackingmentioning
confidence: 99%
See 1 more Smart Citation
“…In (6) , γ(d, ∇d) is the crack density function per unit volume (see e.g. Miehe et al (2010);Nguyen et al (2015)), defined by:…”
Section: Phase Field Modeling Of Stress Corrosion Crackingmentioning
confidence: 99%
“…For more details and practical implementation aspects, the interested reader may refer to Miehe et al (2010); Nguyen et al (2015). The phase field method is based on a regularized formulation of a sharp crack description.…”
Section: Phase Field Modeling Of Stress Corrosion Crackingmentioning
confidence: 99%
“…For more details and practical implementation aspects, the interested reader can refer to [14,20]. The phase field method is based on a regularized formulation of a sharp crack description.…”
Section: Phase Field Modelling Of Quasi-brittle Microcrackingmentioning
confidence: 99%
“…They possess a sound mathematical background and a variational structure. Recent attempts to study fracture in cementitious materials using phase-field modeling are reported in [35,36], while in [7] a phase-field model of fracture is coupled with diffusion, with special focus on chloride diffusion in cement paste.…”
Section: Introductionmentioning
confidence: 99%